POVERTY REVISITED: PRESENTING POVERTY THE NORMATIVE WAY - S. Saidu, Oluwaseun (Jurnal Syariah, 2017)
This paper delves into the issue of poverty from the Islamic perspective. Particularly, the author aims to present the concept of poverty in the “normative” [as it ought to be] way and enquires whether concerns regarding poverty, or the state of poverty, is for Muslims a justified issue. In other words, are the absence of material supplies and wealth widely seen today in a negative light or is it the real or true poverty - as represented by the Qur’ān (Allah) and (Sunnah) His Messenger (PBUH) - really the poverty worth focusing on? Without adequately understanding what poverty is there cannot be effective solutions and interventions. Employing scriptural evidence vis-à-vis Islamic legal reasoning, we argue that normative poverty, in accordance with the Islamic tradition, is the real poverty and not material poverty.